2011
DOI: 10.1016/j.ejpain.2011.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Review: Electrical spinal cord stimulation in painful diabetic polyneuropathy, a systematic review on treatment efficacy and safety

Abstract: Available literature shows promising results for the pain-relieving effect of spinal cord stimulation in painful diabetic polyneuropathy. The outcome of a randomized clinical trial is needed before spinal cord stimulation can be considered to be integrated in the standardized treatment algorithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…At 1-year follow-up, 63% of the patients had more than 50% pain reduction. In addition, analgetic medication could be stopped in 60% of the patients 97. Recently, long-term effects for SCS for diabetic polyneuropathy were shown over a follow-up of 3 years 98…”
Section: Indicationsmentioning
confidence: 99%
“…At 1-year follow-up, 63% of the patients had more than 50% pain reduction. In addition, analgetic medication could be stopped in 60% of the patients 97. Recently, long-term effects for SCS for diabetic polyneuropathy were shown over a follow-up of 3 years 98…”
Section: Indicationsmentioning
confidence: 99%
“…[33] Studies on the effect of SCS for inoperable CLI caused by diabetes mellitus are performed. Four studies [34] and a systematic review [35] have shown promising pain-relief effect after spinal cord stimulation in patients with longterm diabetic polyneuropathy.…”
Section: Effi Cacy Of Scsmentioning
confidence: 99%
“…Spinal cord stimulation was also beneficial for patients with painful diabetic polyneuro pathy [49]. Cost-effectiveness studies have also favored spinal cord stimulation.…”
Section: Spinal Cord Stimulationmentioning
confidence: 97%